(untitled) (Dhaka University Law Journal, 2026)
This article reconstructs vyavahāra as a procedural jurisprudence that gives institutional life to Dharma by organising adjudication around reasoned decision, structured proof, and calibrated remedy. Drawing on the Smṛti and Dharmasūtra corpora and the Arthaśāstra, it maps a four-source architecture of legality: Dharma, vyavahāra, cāritra (custom), and rājaśāsana (royal ordinance). The analysis shows how this ordering disciplines discretion while orienting judgment towards ethical ends. It interprets the vyavahāra-mātrikā of eighteen titles as an early taxonomy of causes of action and remedial fit; reconstructs the lifecycle of a suit from plaint to decree; and reads evidentiary canons through pramāṇa theory with attention to burdens, credibility, and probative hierarchies. The article argues that the tradition contains recognisable safeguards of due process, including impartial composition, audi alteram partem, reasons-giving, and transparent record-keeping, yet it also embeds status hierarchies of caste and gender that are normatively non-portable. A comparative conversation with modern Indian procedure and evidence clarifies what can travel: the craft ethos of issue-framing, reliability-first proof, proportional sanction, supervised settlement, and accessible records. The conclusion proposes a design ledger for contemporary institutions that carries forward these transferable principles, rejects status-based exclusions, and redesigns communitarian mechanisms under rights-compliant oversight. The result is a historically grounded account of process that speaks to present debates on fairness and institutional legitimacy. Dhaka University Law Journal, 2025, 36(2), 53-75